Factors that Influence the Acceptance of Telemedicine Services in Rural Community Through an Extended Technology Acceptance Model (TAM) (Journal of Business and Management, 2022)
Since the COVID-19 pandemic, telemedicine has increasingly become an important role in health care services. Telemedicine has the potential to be a solution in overcoming health service problems during a pandemic, especially in improving health care services in remote areas. However, the benefits of telemedicine can only be felt when people begin to accept and use it proactively. Therefore, it is important to know the factors that influence the acceptance of telemedicine. The main objective is to investigate the factors influencing the acceptance of telemedicine services in rural communities. TAM theory by Davis (1989) was used as a theoretical framework for this research. The data is collected through a quantitative approach using a questionnaire-based survey, and PLS-SEM method. The results found that PU, and PEOU, have a significant effect on AT. Moreover, SI and AT have a significant effect on BI while PR, trust, TA, resistance to use, and FC do not have a significant effect on BI. The findings of this study can be used as material for consideration in the development and design of telemedicine services in rural communities.Keywords: Behavioral Intention, Partial Least Square (PLS), Perceived Ease of Use, Rural Communities, Technology Acceptance Model (TAM), Telemedicine